2011
DOI: 10.1016/j.pec.2010.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Does questionnaire-based patient feedback reflect the important qualities of clinical consultations? Context, benefits and risks

Abstract: Doctors should consider the transactional or relational preference of a patient in approaching a consultation. Patient feedback can deliver benefits to doctors and patients, but risks must be acknowledged and mitigated against.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Whilst gathering patient feedback maybe an acceptable and appropriate way of evaluating the practitioner's communication skills, doctors have reported finding it stressful, and indicated they may target specific patients or sessions or they may even alter their behaviour in the knowledge that feedback is being sought. 15 In our research this may also have been influenced by each practitioners' enthusiasm for or belief in the process, concerns or fears associated with the collection of feedback and engagement or their general willingness and ability to comply with prescribed tasks. In this study, although the number of forms collected per student was not attributed, the distribution of cards was initiated by the supervising clinician, so this effect would be minimised.…”
Section: Discussionmentioning
confidence: 87%
“…Whilst gathering patient feedback maybe an acceptable and appropriate way of evaluating the practitioner's communication skills, doctors have reported finding it stressful, and indicated they may target specific patients or sessions or they may even alter their behaviour in the knowledge that feedback is being sought. 15 In our research this may also have been influenced by each practitioners' enthusiasm for or belief in the process, concerns or fears associated with the collection of feedback and engagement or their general willingness and ability to comply with prescribed tasks. In this study, although the number of forms collected per student was not attributed, the distribution of cards was initiated by the supervising clinician, so this effect would be minimised.…”
Section: Discussionmentioning
confidence: 87%
“…Included studies reported: a change in organisational practice ( n =1, Kirkpatrick level 4a) [ 7 ]; a measured change in behaviour ( n =6, Kirkpatrick level 3b) [ 13 , 50 54 ]; self-reported change or intention to change ( n =12, Kirkpatrick level 3a), [ 2 , 8 , 10 , 11 , 17 , 55 – 61 ] and acquisition of knowledge or skills ( n =1, Kirkpatrick level 2b) following the provision of patient feedback [ 1 ]. No studies identified a change at the highest evaluation level – a change in the health and wellbeing of patients (Kirkpatrick level 4b).…”
Section: Resultsmentioning
confidence: 99%
“…One study identified a change in knowledge acquisition/understanding [ 1 ]. Doctors involved in this study reported learning about the importance of trust, consultation style and communication [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations